DIGITAL IJTIHAD QAWAʿIDI: A MAQAṢIDIC EPISTEMOLOGY FOR BLOCKCHAIN-BASED ISLAMIC LEGAL SYSTEMS - Achmad Nursobah (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study proposes a novel epistemological framework in Islamic legal theory termed Digital Ijtihad Qawaʿidi, an integrative model that embeds qawaʿid fiqhiyah (legal maxims) and maqaṣid al-shariʿah (higher objectives of Islamic law) into blockchain-based legal architectures. Employing a qualitative–philosophical approach within a transdisciplinary framework, the research synthesizes uṣul al-fiqh epistemology, digital ethics, and the philosophy of technology. The study argues that the rise of autonomous algorithmic systems necessitates a paradigmatic shift from fiqh al-naṣṣ (text-centered legal reasoning) toward fiqh al-niẓam al-raqami (digital system–based legal reasoning). The proposed model consists of three interrelated stages: takyif al-waqiʿ al-raqami (analysis of digital structures), tanzil al-qawaʿid ʿala al-waqiʿ (operationalization of legal maxims within system functions), and taḥqiq al-maqaṣid al-raqamiyyah (evaluation of maqaṣid-oriented outcomes). Through conceptual mapping and illustrative cases namely SukukChain, ZakatChain, and Halal Chain this study demonstrates that qawaʿid fiqhiyah can be translated into algorithmic norms capable of ensuring legal certainty (yaqin), justice (ʿadl), and trust (amanah). This research contributes to the epistemological reconstruction of Islamic law in the context of non-human decision-making systems and establishes a maqaṣidic foundation for Shariah-oriented blockchain governance. Accordingly, Islamic law is repositioned not merely as a passive observer of technological change, but as an active normative framework shaping global digital ethics.